Environmental saving potentials of a smart home system from a life cycle perspective: How green is the smart home?. (20th August 2021) - Pohl, Johanna; Frick, Vivian; Hoefner, Anja; Santarius, Tilman; Finkbeiner, Matthias
Abstract: By improving energy management, smart home applications may reduce household energy consumption. This study therefore examines environmental saving potentials of a smart home system (SHS) with smart heating in Germany from a life cycle perspective. Research on the energy saving potential of an SHS usually focuses on single applications rather than the entire system and hence misses life cycle impacts of the system itself. To overcome this limitation, this study takes an interdisciplinary user-driven approach. We conduct an LCA of an average SHS in Germany that includes smart heating for five heating energy saving scenarios. The components of a representative SHS were determined by an online survey among users of smart homes with smart heating (N = 375) in Germany. As a precondition, net savings can only be achieved when the environmental effects from savings in household heating energy exceed the effects from producing and operating an SHS. The results of our case study for the impact categories Climate Change (GWP), Primary Energy Demand (PED), Abiotic Depletion (ADP) and Ecotoxicity (Ecotox) are heterogeneous: we show that savings of GWP and PED can be achieved by an SHS that includes smart heating. However, minimum savings of 6% of annual heating energy over 3.1 years for PED and over 2.4 years for GWP need to be realised by an SHS in order to exceed the environmental effects caused by their production and operation. For ADP and Ecotox, the smart home represents a further environmental burden. We show that including both the life cycle perspective and user-driven parameters is crucial when determining the total environmental effects of smart homes. Future research should further explore these links between the user perspective and LCA. Highlights: Interdisciplinary framework combines social science and environmental assessment. Holistic assessment of direct and indirect environmental effects of smart homes. Analyses of potential burden shifting through implementing smart homes. Net savings of smart homes are much smaller than actual savings in heating energy.